Catastrophic Intracardiac Thrombosis During Emergency Repair of an Expanding Aortic Pseudoaneurysm: A Case Report. Issue 9 (1st November 2019) - Vadlamudi, Ratna; Chan, Jay; Sniecinski, Roman M.
Abstract : Catastrophic thrombosis is a rare but frequently fatal event following complex cardiac surgery. It is most often encountered following separation from cardiopulmonary bypass (CPB) and reversal of heparin anticoagulation, and somewhat paradoxically, at the time when bleeding from post-CPB coagulopathy is being treated. We report the case of a 41-year-old female taken to the operating room for repair of an expanding ascending aortic pseudoaneurysm. Following a prolonged operation, she developed intracardiac thrombus during transfusion of hemostatic blood products and procoagulant agents. Potential contributing factors are discussed. Abstract : Supplemental Digital Content is available in the text.